Design and Validation of Psychoeducational Guidance Service Package: An Effort to Enhance Elementary School Students' Learning Motivation - Musfirah, Musfirah; Arismunandar; Abdul Saman (Cita konsultindo, 2025)
Psychoeducational services at the elementary school level play a crucial role in enhancing students' learning motivation. This study aims to design and test the validity of a psychoeducational guidance service device that can support the improvement of students' learning motivation. The research uses a development research method with the Four-D model, which consists of four stages: Define, Design, Develop, and Disseminate. The primary focus of this study is on the design and validation stages of the service device, which includes service implementation plans, materials, Student Work Sheets (LKPD), evaluation, and motivational instruments. The validation of the device was conducted by subject matter experts and media experts. The validation results indicate that the psychoeducational guidance service device received very appropriate scores from both subject matter and media experts. Specifically, the motivational instruments and psychoeducational media demonstrated excellent quality in enhancing student motivation. Overall, this service device is deemed highly suitable for implementation in psychoeducational guidance processes at the elementary school level. This study contributes to the development of effective guidance devices aimed at improving students' learning motivation in elementary schools